A disciplina carcerária na sociedade de controle: uma análise genealógica do Regime Disciplinar Diferenciado - Santana, Aline Passos de Jesus (2011)
The Differentiated Disciplinary Regime (RDD) and the Prison Rehabilitation Center of President Bernardes (CRP) are punitive practices that have altered the configuration of prison discipline in Brazil. Such practices do not indicate the preponderance of the disciplinary aspects of incarceration as it used to be, but the problem of their efficient management, which no longer is restricted to custodial sentences in enclosed spaces. It is a strategy of control focused less on each person and more on the ways in which they live and by how they relate to it. At stake is the expansion of the surface of contact between governments and the governed. This dissertation intends to show how the RDD and the CRP were gestated from a progressive strengthening of the institutional prison administration, related to the sharing of duties with other managers of legalisms and illegalisms. Nowadays, we understand that the shared government of prisons is inseparable from the continuity and their expansion, either as maximum-security prisons or by the proliferation of open-air controls. We affirm that the re-diminishment of prison discipline, in these terms, makes the boundaries between both the inside and outside of prisons each day less discernible. We highlight that the notion of maximumsecurity was rediminished by the devices of electronic control at the same time as the last ones started to be used for the repeated application of the so-called alternative sentencing. Therefore, we are interested in the penal abolitionism and in its strategies as singular possibilities to intercept and destroy imprisonment more or less subtle. We problematize the capture of the abolitionists strategies and highlight the urgency to invent new paths separate from the regime of punishments